A cascade of failures: the U.S. Army and the Japanese-American internment decision in World War II - Thomsen, Paul A. (Kansas State University, 2013)
The Second World War internment of the West Coast Issei and Nisei remains a tragic moment in American history. It has long been viewed by historians as a singular act of mass social and political pressure to remove a racially constructed social group from the area, but it was carried out by the United States Army under the direction of the War Department. This dissertation studies the formation of the military policy that led to the Second World War internment of Japanese-Americans and the transformation of a reluctant American Army into an agent of a xenophobic West Coast civilian populace through external pressure, poor planning, and false assumptions. This study focuses on several aspects of civil-military relations associated with the Second World War internment of the Issei and Nisei. This includes the history of militancy and mob rule in the West Coast urban landscape and the borders of civil-military relations on the West Coast as they applied to the region’s xenophobic legislative government. Likewise, the relationship between the military and the militia, urban race relations, and the role of intelligence analysis play a central role in determining the distortion of facts, which shaped the American military’s internment policy. Finally, the disconnects between the East and West Coast arms of the federal government and the Justice and War Departments play an equally pivotal role steering the military’s response to the devolving state of affairs on the West Coast in the months following Pearl Harbor, resulting in the internment of over 110,000 Issei and Nisei in the following months.
Keywords: United States Army; West Coast; Nisei; Issei; Second World War; Military History (0722)